The ex officio evidence in the Peruvian labor process - Arévalo Vela, Javier (2021)
This article develops the topic of ex officio evidence through the analysis of article 22 of the New Labor Procedure Law, with the supplementary application of the civil procedure regulations. Its constitutional and legal limits are delimited, in addition to the conditions that must be met for the labor judge to order the performance of the ex officio evidence.